Learn more about

Refine search

Results (displaying matches 1-50 of 2295) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
847.d.847.1 847.d \(y^2 + (x^3 + x^2 + x + 1)y = -12x^6 - 15x^5 + 9x^4 + 31x^3 + 9x^2 - 15x - 12\) $G_{3,3}$ 0
997.b.997.1 997.b \(y^2 + y = x^5 - 2x^4 + 2x^3 - x^2\) $\mathrm{USp}(4)$ 1
1083.a.1083.1 1083.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^3\) $G_{3,3}$ 1
1083.a.20577.1 1083.a \(y^2 + x^3y = x^5 - 5x^4 + 11x^3 - 13x^2 + 9x - 3\) $G_{3,3}$ 1
1369.a.1369.1 1369.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^4 - x^3 - x^2\) $G_{3,3}$ 1
1369.a.50653.1 1369.a \(y^2 + x^3y = 2x^5 - 5x^4 + 7x^3 - 6x^2 + 3x - 1\) $G_{3,3}$ 1
1444.b.109744.1 1444.b \(y^2 + x^3y = -4x^4 + 16x^2 - 19\) $G_{3,3}$ 0
1636.a.6544.1 1636.a \(y^2 + (x^3 + x)y = -x^4 - x^3 + x^2 + x\) $\mathrm{USp}(4)$ 1
1854.a.11124.1 1854.a \(y^2 + (x^3 + x^2 + x)y = -2x^3 - 2x^2 + x + 1\) $\mathrm{USp}(4)$ 1
1870.a.226270.1 1870.a \(y^2 + (x + 1)y = -2x^6 + x^5 - x^4 + 9x^3 - 2x^2 + 2x - 9\) $\mathrm{USp}(4)$ 0
1900.a.3800.1 1900.a \(y^2 + (x^3 + x + 1)y = x^3 - x\) $\mathrm{USp}(4)$ 1
2031.a.6093.1 2031.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^4 - x\) $\mathrm{USp}(4)$ 1
2059.a.2059.1 2059.a \(y^2 + y = x^5 - 4x^4 + 4x^3 - x\) $\mathrm{USp}(4)$ 1
2148.a.77328.1 2148.a \(y^2 + (x^3 + x)y = x^4 - 3x^3 + 3x^2 - x\) $\mathrm{USp}(4)$ 1
2172.a.4344.1 2172.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2312.a.4624.1 2312.a \(y^2 + xy = x^6 - 2x^4 - x^3 + x^2 + x\) $\mathrm{USp}(4)$ 1
2312.a.18496.1 2312.a \(y^2 + (x + 1)y = x^6 - x^4\) $\mathrm{USp}(4)$ 1
2341.a.2341.1 2341.a \(y^2 + y = x^5 + 2x^4 + 2x^3 - x - 1\) $\mathrm{USp}(4)$ 0
2556.a.30672.1 2556.a \(y^2 + x^3y = -2x^4 - 2x^3 + x^2 + 2x + 1\) $\mathrm{USp}(4)$ 1
2634.a.2634.1 2634.a \(y^2 + (x + 1)y = -x^5 + x^4 - 2x^2 + x - 1\) $\mathrm{USp}(4)$ 0
2697.a.2697.1 2697.a \(y^2 + (x^3 + x + 1)y = x^5 - 2x^3 - x^2 - 1\) $\mathrm{USp}(4)$ 0
2859.a.77193.1 2859.a \(y^2 + (x^3 + x + 1)y = 2x^5 + 4x^4 + x^3 + 2x^2\) $\mathrm{USp}(4)$ 1
2888.a.5776.1 2888.a \(y^2 + y = x^6 + x^4 + x^2\) $G_{3,3}$ 1
2891.a.2891.1 2891.a \(y^2 + y = x^5 - 2x^4 + x^2\) $\mathrm{USp}(4)$ 1
2985.a.134325.1 2985.a \(y^2 + y = x^5 + x^4 + 2x^2\) $\mathrm{USp}(4)$ 1
3012.a.6024.1 3012.a \(y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 4x^4 + 3x^3 - 3x^2 + x - 1\) $\mathrm{USp}(4)$ 0
3026.a.3026.1 3026.a \(y^2 + (x + 1)y = x^5 - 3x^4 + 3x^2 + x\) $\mathrm{USp}(4)$ 1
3172.a.12688.1 3172.a \(y^2 + x^3y = x^2 - 2x + 1\) $\mathrm{USp}(4)$ 1
3209.a.3209.1 3209.a \(y^2 + (x^2 + x + 1)y = x^5 - 2x^4 + x^3 - 3x^2 - 1\) $\mathrm{USp}(4)$ 0
3381.a.165669.1 3381.a \(y^2 + y = x^5 - 4x^3 - 7x^2 - 4x - 1\) $\mathrm{USp}(4)$ 0
3388.b.13552.1 3388.b \(y^2 + x^3y = -2x^4 + 6x^2 - 7\) $G_{3,3}$ 1
3392.b.27136.1 3392.b \(y^2 + (x + 1)y = x^6 + x^4 - x^3 - x^2\) $\mathrm{USp}(4)$ 1
3564.b.705672.1 3564.b \(y^2 + (x^3 + x + 1)y = 2x^2 + 4x + 2\) $\mathrm{USp}(4)$ 1
3601.b.608569.1 3601.b \(y^2 + (x^3 + x + 1)y = -x^4 + 2x^3 - 3x + 7\) $\mathrm{USp}(4)$ 0
3645.a.10935.1 3645.a \(y^2 + x^3y = x^3 + 3x^2 + 3x + 1\) $N(G_{1,3})$ 1
3645.a.295245.1 3645.a \(y^2 + (x^3 + x^2 + x + 1)y = x^5 - 7x^3 + x\) $N(G_{1,3})$ 1
3709.a.3709.1 3709.a \(y^2 + (x^3 + x + 1)y = -x^5 - x^2 - x\) $\mathrm{USp}(4)$ 1
3716.a.7432.1 3716.a \(y^2 + (x^3 + x^2 + 1)y = x^4 + 2x^3 - x\) $\mathrm{USp}(4)$ 1
3732.a.67176.1 3732.a \(y^2 + (x^3 + x + 1)y = -x^4 + x\) $\mathrm{USp}(4)$ 1
3860.a.77200.1 3860.a \(y^2 + x^3y = 4x^2 - 4x + 1\) $\mathrm{USp}(4)$ 1
3872.b.495616.1 3872.b \(y^2 + (x^3 + x^2 + x + 1)y = -x^4 + 2x^3 - x^2\) $G_{3,3}$ 1
3908.a.15632.1 3908.a \(y^2 + (x^3 + x^2 + x + 1)y = -2x^2 - 2x + 1\) $\mathrm{USp}(4)$ 1
3940.a.15760.1 3940.a \(y^2 + y = x^6 + x^2 - x\) $\mathrm{USp}(4)$ 1
3973.a.3973.1 3973.a \(y^2 + y = x^5 + 2x^4 + 4x^3 + 4x^2 + 3x + 1\) $\mathrm{USp}(4)$ 0
4036.a.16144.1 4036.a \(y^2 + x^3y = x^4 - 2x^3 + 3x^2 - 2x + 1\) $\mathrm{USp}(4)$ 1
4100.a.65600.1 4100.a \(y^2 + (x^3 + x + 1)y = x^6 + 3x^5 + 6x^4 + 6x^3 + 6x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
4178.a.4178.1 4178.a \(y^2 + (x^3 + 1)y = -2x^4 + 6x^2 - x - 6\) $\mathrm{USp}(4)$ 1
4252.a.68032.1 4252.a \(y^2 + (x^3 + 1)y = x^4 - x^2 - x\) $\mathrm{USp}(4)$ 1
4293.a.4293.1 4293.a \(y^2 + y = x^5 - x^4 - 2x^3 + 7x^2 - 7x + 3\) $\mathrm{USp}(4)$ 0
4332.a.17328.1 4332.a \(y^2 + y = x^6 - 2x^4 + 2x^2 - 1\) $G_{3,3}$ 1
Next

Download all search results for